Integrated Diseases Management and plant Health - Gupta V.K.; Sharma R.C. (Jodhpur Scientific publishers, 2011)
it deals with the integrated diseases management and plant health
tilletia foetida wheat loose smut
Keywords: tilletia foetida wheat loose smut